2005
DOI: 10.33899/rden.2005.45508
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effect of water extraction of Salvadora persica (Miswak) as a root canal irrigant

Abstract: The aim of this study was to evaluate the antimicrobial effect of 10% water extraction of Salvadora persica (Miswak) when used clinically as an endodontic irrigant. Twenty four uniradicular teeth with necrotic pulps were chosen. The patients were divided randomly into 2 groups: Experimental group, in which water extract of Salvadora persica (10%) was used as a root canal irrigant; and control group, in which distilled water was used as a root canal irrigant. Bacteriological samples were obtained from the canal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Ten percent water extraction of Salvadora persica is an effective antimicrobial agent when utilized clinically as an irrigant in the endodontic treatment of teeth with necrotic pulps. 35 Based on their in vitro study, Elangovan et al 36 revealed that aqueous extracts of neem ( Azadirachta indica ) showed the greatest antimicrobial activity against Streptococcus mutans , while miswak ( Salvadora persica ) extracts showed superior antimicrobial activity against Lactobacillus acidophilus . The constituent of Salvadora persica , such as N-benzyl-2-phenylacetamide, had shown moderate antimicrobial activity against Escherichia coli .…”
Section: Therapeutic Effects Of Miswak On Oral Health Antibacterial mentioning
confidence: 99%
“…Ten percent water extraction of Salvadora persica is an effective antimicrobial agent when utilized clinically as an irrigant in the endodontic treatment of teeth with necrotic pulps. 35 Based on their in vitro study, Elangovan et al 36 revealed that aqueous extracts of neem ( Azadirachta indica ) showed the greatest antimicrobial activity against Streptococcus mutans , while miswak ( Salvadora persica ) extracts showed superior antimicrobial activity against Lactobacillus acidophilus . The constituent of Salvadora persica , such as N-benzyl-2-phenylacetamide, had shown moderate antimicrobial activity against Escherichia coli .…”
Section: Therapeutic Effects Of Miswak On Oral Health Antibacterial mentioning
confidence: 99%
“…In another study, Al-Salman et al (23) revealed that 10% water extraction of Salvadora persica is an effective antimicrobial agent when utilized clinically as an irrigant in the endodontic treatment of teeth with necrotic pulps.…”
Section: Discussionmentioning
confidence: 99%
“…Salvadora Persica extract has been shown to be an effective when used as root canal irrigant (14,15) . The results of this work may be beneficial for the treatment of recurrent oral herpes infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that extract of Salvadora Persica possess many biological properties including antibacterial (7) , antifungal (8) , anticaries (7,9) , anti-inflammatory (10) , antiplaque effect (11) , and reduces gingivitis and gingival bleeding (12,13) . Recently Salvadora Persica extract was evaluated as root canal irrigant (14,15) .…”
Section: Introductionmentioning
confidence: 99%